1997
DOI: 10.1076/phbi.35.4.265.13314
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity in Desert Plants of the Negev and Bedouin Market Plant Products

Abstract: Aqueous plant extracts of 63 desert plants collected in the Negev desert and Bedouin market (Beer Sheva) were screened for larvicidal activity. Larvicidal activity was found in 16 plants, of which seven were reported in the ethnobotanical literature to be either poisonous, vermifuge, abortive, or toxic. Seven species showed high toxicity against Aedes aegypti larvae: Ephedra aphylla, Gypsophila arabica, Anabasis articulata, Mesembryanthemum nodiflorum, Nicotiana rustica, Hammada scoparia, Achillea fragrantissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…We have brought together a collection of over 400 plant species mainly from arid lands, traditional Bedouin medicine and the Tel-Aviv Botanical Garden and have prepared solvent extracts of different plants and plant products. 25,26 In order to detect potential anticancer and anti-inflammatory activity, we screened 34 methanol extracts from this collection (Suppl. Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We have brought together a collection of over 400 plant species mainly from arid lands, traditional Bedouin medicine and the Tel-Aviv Botanical Garden and have prepared solvent extracts of different plants and plant products. 25,26 In order to detect potential anticancer and anti-inflammatory activity, we screened 34 methanol extracts from this collection (Suppl. Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, reported that feeding by larval red ßour beetle, Tribolium castaneum (Herbst), on diet mixed with the methanol extracts from P. harmala seeds caused 58% larval mortality and prolonged larval developmental time, whereas feeding by adult T. castaneum on the same diet reduced their progeny production. As a larvicide, aqueous P. harmala extracts had moderate toxicity against Aedes aegypti (L.) larvae (Sathiyamoorthy et al 1997). These studies indicate a potential use of P. harmala extracts for the control of insect species as a possible alternative or companion to the use of synthetic pesticides.…”
mentioning
confidence: 98%
“…It was reported that Nepeta plants were prepared as tea and used in traditional medicine as anthelmintics, febrifuges, expectorants, to treat bronchitis, bites, stings of and scorpions (Arnold et al, 1993). Ballota undulata plant is used by Bedouins as a remedy for the treatment of wounds, scorpion, bee, and wasp stings (Sathiyamoorthy et al, 1997). The aqueous extract of B. undulata was tested for antitumor and antimalarial activities (Sathiyamoorthy et al, 1999).…”
Section: Botany and Microbiology Department Faculty Of Science Al-amentioning
confidence: 99%